2017
DOI: 10.1002/jbmr.3312
|View full text |Cite
|
Sign up to set email alerts
|

Serum Sclerostin Levels in Adults With Osteogenesis Imperfecta: Comparison With Normal Individuals and Response to Teriparatide Therapy

Abstract: Sclerostin (SOST), a glycoprotein primarily derived from osteocytes, is an important regulator of bone remodeling. Osteogenesis imperfecta (OI) is a heritable disorder of bone characterized by low bone mass, bone fragility, recurrent fractures, and bone deformities. Altered SOST-mediated signaling may have a role in pathogenesis of type I collagen-related OI; however, this has not been evaluated in humans. We measured serum SOST levels in adults with OI who were enrolled in a randomized, placebo-controlled cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
(68 reference statements)
0
11
0
1
Order By: Relevance
“…Sclerostin (Scl, SOST) is a protein encoded by the SOST gene that is primarily secreted by osteocytes and is known to be a negative regulator of the bone mass [8,9]. Scl binds to lowdensity lipoprotein receptor-related proteins (LRP) 5, LRP 6, and frizzled receptors to antagonize Wnt/ catenin signaling [10][11][12][13]. Wnt/ catenin signaling is crucial for osteoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Sclerostin (Scl, SOST) is a protein encoded by the SOST gene that is primarily secreted by osteocytes and is known to be a negative regulator of the bone mass [8,9]. Scl binds to lowdensity lipoprotein receptor-related proteins (LRP) 5, LRP 6, and frizzled receptors to antagonize Wnt/ catenin signaling [10][11][12][13]. Wnt/ catenin signaling is crucial for osteoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, there is no clear consensus on whether or not the levels of sclerostin are altered in OI patients, although there is evidence of improved bone properties in several mouse models of OI ( oim/oim [ 27 ], +/G610C , Brtl −/− [ 122 ], Col1a1 +/Jrt [ 123 ], and Crtap −/− [ 124 ]) subjected to sclerostin inhibition. Patient clinical trials utilizing anti-sclerostin antibodies are currently ongoing with initial results showing increased markers of bone formation and reduced markers of bone resorption [ 2 , 15 , 18 , 125 , 126 ].…”
Section: Muscle–bone Crosstalkmentioning
confidence: 99%
“…It was recently shown that serum levels of DKK1 are indeed elevated in children with OI [ 32 ]. While sclerostin serum levels were found normal or even decreased in OI patients [ 33 , 34 , 35 ], treatment with sclerostin antibody increased bone mass and improved bone mechanical strength in diverse mouse models and in patients [ 36 , 37 , 38 ]. In addition, the profoundly perturbed osteoblasts in OI might also sense and react differently to sclerostin or other local factors.…”
Section: Introductionmentioning
confidence: 99%